The risks of long-term use of proton pump inhibitors: a critical review - Megan Jaynes; Avinash B. Kumar (SAGE Publishing, 2019)
Proton pump inhibitors (PPIs) are among the most frequently prescribed medications. Their use is likely even higher than estimated due to an increase in the number of PPIs available without a prescription. Appropriate indications for PPI use include Helicobacter pylori infection, erosive esophagitis, gastric ulcers, and stress ulcer prevention in high-risk critically ill patients. Unfortunately, PPIs are often used off-label for extended periods of time. This increase in PPI usage over the past two decades has called into question the long-term effects of these medications. The association between PPI use and infection, particularly Clostridium difficile and pneumonia, has been the subject of several studies. It's proposed that the alteration in gastrointestinal microflora by PPIs produces an environment conducive to development of these types of infections. At least one study has suggested that long-term PPI use increases the risk of dementia. Drug interactions are an important and often overlooked consideration when prescribing any medication. The potential interaction between PPIs and antiplatelet agents has been the subject of multiple studies. One of the more recent concerns with PPI use is their role in the development or progression of chronic kidney disease. There is also some literature suggesting that PPIs contribute to the development of various micronutrient deficiencies. Most of the literature examining the potential adverse effects of PPI use is composed of retrospective, observation studies. There is a need for higher quality studies exploring this relationship.